Constitutional crisis in the bicentennial of Peru - Mendívil Nina, José (2021)
Peru is now in the middle of a constitutional crisis that must be resolved through a constitutional process of reforms or amendments to the political regime, the use of natural resources, and the distribution of power among the different government agencies throughout our territory. This crisis has been caused by the continuous confrontation between the President and the Congress since 2016. Such clash has been aggravated by the judgments rendered by the Constitutional Court which ratified as constitutional the arbitrary the “factual denial” to the non-vote of confidence that led to the dissolution of Congress. The current Administration is attempting to leverage upon this precedent to impose a Marxist-Leninist socialist regime to replace the republican system that has been in place for 200 years.